Recent Stimulant Use and Leukocyte Gene Expression In Methamphetamine Users with Treated HIV Infection - Carrico, Adam W. (Brain Behav Immun, 2018)
Stimulant use may accelerate HIV disease progression through biological and behavioral pathways. However, scant research with treated HIV-positive persons has examined stimulant-associated alterations in pathophysiologic processes relevant to HIV pathogenesis. In a sample of 55 HIV-positive, methamphetamine-using sexual minority men with a viral load less than 200 copies/mL, we conducted RNA sequencing to examine patterns of leukocyte gene expression in participants who had a urine sample that was reactive for stimulants (n = 27) as compared to those who tested non-reactive (n = 28). Results indicated differential expression of 32 genes and perturbation of 168 pathways in recent stimulant users. We observed statistically significant differential expression of single genes previously associated with HIV latency, cell cycle regulation, and immune activation in recent stimulant users (false discovery rate p < 0.10). Pathway analyses indicated enrichment for genes associated with inflammation, innate immune activation, neuroendocrine hormone regulation, and neurotransmitter synthesis. Recent stimulant users displayed concurrent elevations in plasma levels of tumor necrosis factor – alpha (TNF-α) but not interleukin 6 (IL-6). Further research is needed to examine the bio-behavioral mechanisms whereby stimulant use may contribute to HIV persistence and disease progression.